PENENTUAN PREMI DAN CADANGAN MANFAAT ASURANSI JIWA KREDIT PADA BANK UMUM - DAMAYANTHI, NI LUH ROSITA; WIDANA, I NYOMAN; SARI, KARTIKA (E-Jurnal Matematika; Vol 12 No 1 (2023)DO - 10.24843/MTK.2023.v12.i01.p400, 2023)
Credit life insurance provides protection and guarantees to policyholders as debtors within the coverage period. Each insurance participant is required to pay premiums on time, namely at the beginning before the credit is issued by the bank. Net premiums can be determined using annuity calculations using the equivalence principle. Premium payments on credit life insurance are made at once taking into account mortality based on age, gender, and interest rates of 15.5% and 10.26% with a loan term of 8 years. The results of the analysis of the single premium value for the interest rate of 15.5% and 10.26% at the age of 36, 44, and 52 years showed that the interest rate and age had an effect on the premium price. The obligation of the insurance company is to pay claims to insurance participants. Insurance companies are required to have a benefit reserve fund to anticipate excess claims. Benefit reserves are the amount of money collected by the insurance company during the coverage period in preparation for claim payments. The calculation of benefit reserves in this study uses the prospective method. In the large calculation of the benefit reserves for interest rates of 15.5% and 10.26% at the age of 36, 44, and 52 years, the value of the benefit reserves decreased from the first year to the last year.